Requisitos para o planejamento da estratégia de operação na implementação da transformação digital - Costa, Georgiana Motta (Universidade do Vale do Rio dos Sinos, 2021)
This research has as its object of study, the relationship of the digital transformation process and its planning as a driver for deployments. The “Design Science Research” Method was used as a research strategy. The requirements considered relevant in the planning of implantation of digital transformations were analyzed, systematized in the studied theoretical Framework, as well as, reflected in a delimited group of executives, working in participating organizations in Brazil, who went through a process of this nature and / or which are experiencing. The general objective is to develop an Orientative Framework that contributes to the analysis of the requirements necessary for the Planning of the Digital Transformation Operation Strategy. A Framework for Digital Transformation Planning was produced, which is called “CPAS – CHECKING, PLANNING, APPLYING, SUSTAINING” – DIGITAL TRANSFORMATION IN BUSINESS. In addition, a method for monitoring and evaluating the performance of these requirements considered in the Framework was developed, to be applied during the implementation process of Digital Transformation.
Keywords: Transformação digital; Design science research; Estratégia de operações; Requisitos para transformação digital; Framework transformação digital; Digital transformation; Operations strategy; Requirements for digital transformation; Digital transformation framework; ACCNPQ::Ciências Sociais Aplicadas::Administração